Water management for rice production: a key component of food security in East Africa - Denis Bwire; Hirotaka Saito; Roy C. Sidle; Moses Mugisha (Discover Water)
Abstract Water is a valuable resource for rice production, which is an integral component of food security in East Africa (EA). Rice farming is expanding in the region, with up to 90% produced on smallholder farms using traditional flooding and rain-fed methods, vulnerable to climate change and variability. Despite EA's enormous agricultural and crop potential, the region largely depends on rice imports (> 500,000 tons annually) from Asia due to rising gaps between production and consumption. Sustainable water management practices, including alternate wetting and drying (AWD), system of rice intensification (SRI), and drip irrigation are critical for paddy and upland rice production although practiced at micro-research levels with limited adoption of such technologies by smallholder farmers. Herein, we synthesize key information on smallholder irrigation agriculture development and implications for food security in changing climates in the four EA countries (Uganda, Kenya, Tanzania and Ethiopia), based on scientific literature and reports. Several studies indicate water scarcity is a major threat to rice production, while poverty and food insecurity are linked to low agricultural productivity. Although rice production has increased since 2000 because of the slight expansion of irrigation, yields are still low due to insufficient irrigation development, climate change, and variability and poor agronomic practices. Nonetheless, climate-smart water management technologies such as AWD, SRI, and drip irrigation are less used by paddy and upland rice smallholder farmers for several reasons including limited awareness, funding, and technical knowledge. Therefore, commitments of government sectors, NGOs, farmer-based organizations, and private sectors with clear policies are needed to enhance technology transfer, action research, farmer training, and innovation development. These actions are vital to promote knowledge generation and the adoption of technologies to improve water management for increased rice yields, livelihoods, and food security in changing climates.